The Effect of Community Based Anti Hypertension Exercise on Increasing Awareness and Participation of Elderly People in Stroke Prevention - Erni Rahmawati; Astri Yunita; Dwi Rahayu; Prima Trisna Aji; Erwin Yektiningsih (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Background, The community-based approach emphasises social empowerment in health interventions so that they are more accessible to older adults in their own environment. Purpose: To determine the effect of community-based anti-hypertension exercises on increasing older adults' awareness and participation in stroke prevention. Methods: Quasi-experimental design with a one-group pre-post test design. The research sample consisted of 45 elderly respondents from Singgahan Hamlet. The independent variable was anti-hypertensive exercises, while the dependent variables were awareness and participation. The research instruments were observation sheets and questionnaires. Data were analysed using univariate analysis, data normality, and bivariate analysis. Results: The most common category for the awareness variable among the elderly before the intervention was moderate, at 48.9%, which then increased to high after the intervention, at 55.6%. The most common category in the elderly participation variable before the intervention was moderately active (48.9%), which then increased to active (60.0%) after the intervention. The results of the Wilcoxon test showed that community-based anti-hypertension exercises had an effect on increasing awareness (p=0.000) and participation of the elderly in stroke prevention (p=0.000). Discussion: This approach reduces the psychological and physical barriers for the elderly to participate in health activities. Social support from fellow elderly people and community facilitators strengthens motivation and a sense of belonging to the programme. Conclusions: Community-based anti-hypertension exercises have an effect on increasing awareness and participation among the elderly in stroke prevention.